New Fisheries-related data from the Mediterranean Sea (April 2014) - STERGIOU, K.; BOBORI, D.C.; EKMEKÇİ, F.G. and GÖKOĞLU, M. and KARACHLE, P.K. and MINOS, G. and ÖZVAROL, Y. and SALVARINA, I. and TARKAN, A.S. and VILIZZI, L. (Mediterranean Marine Science, 2014)
As part of its policy, Mediterranean Marine Science started from 2014 to publish a new series of collective article with fisheries-related data from the Mediterranean Sea. In this first collective article we present length frequencies and weight-length relationships for the northern brown shrimp Farfantepenaeus aztecus in the eastern Mediterranean, length-weight relationships for 10 fish species in the North Aegean Sea, the feeding habits for 11 sparid fishes in the North Aegean Sea, a review of the existing literature on the feeding and reproduction of common carp Cyprinus carpio in Anatolia (Turkey) and mouth dimensions and the relationships between mouth area and length for seven freshwater fishes from Lake Volvi (Northern Greece).